Cyril Ramaphosa and the rhetoric of a coordinated African response to the Covid-19 (The Strategic Review for Southern Africa, 2021)
The unprecedented eff ects of Covid-19 have been felt in the whole world. The impact of the pandemic has drawn sharp fault lines of the world’s inequalities. Covid-19 has changed the Global North and the Global South’s social life, respectively. Whilst Covid-19 appeared to spread rapidly in certain parts of the world, and it seemed as if the pandemic would spare Africa. The state of world aff airs has made African governments feel uncomfortable. Some African governments have started making pronouncements given the long-standing grievances about the region’s status in global aff airs. African governments have seen that the threats of the spread of Covid-19 demands collective and individual action. The geopolitical tussle leaves the developing countries stranded in the new economic order. Covid-19 has shaken the foundations of various institutions and states. Africa’s profound failings are noticeable in public health, food security, governance and infrastructural development. Effective coordination of the Covid-19 crisis requires functioning state institutions, application of judiciary norms, and balancing power for the practice to adapt to the realities across the African continent. The second wave of Covid-19 requires the African Union to use this opportunity to integrate its economic pillars into the Africawide response strategy by using Regional Economic Communities (RECs) and the sub-regional blocs of African countries that have existed for decades. The paper concludes that various isolated eff orts made by African countries to deal with the disease and the failure of the continent to adopt a coordinated effort in responding to Covid-19 remain a major challenge. It then recommends that there should be a coordinated approach that goes beyond the rhetoric espoused by South Africa’s President Cyril Ramaphosa in his capacity as AU Chairperson.